NEW PERSPECTIVES ON DIABETIC PERIPHERAL NEUROPATHY AND THE ROLE OF GLYCEMIC CONTROL (International Journal of Food and Nutritional Sciences, 2022)
Diabetes mellitus is characterized by elevated blood sugar, which results in numerous macrovascular and microvascular complications. Additionally, it is a known cause of peripheral neuropathy (PN). This evaluation illustrates the significance of peripheral neuropathy detection in clinical practice. Neuropathy is a common and expensive consequence of both type 1 and types 2 diabetes. Neuropathy is predicted to present in approximately 8% of newly diagnosed individuals and over 50% of people with chronic illnesses. Diabetes neuropathy symptoms may manifest as somatic, autonomic, motor, or sensory problems. The most prevalent type of distal sensory polyneuropathy affects the distal lower extremities and hands in a "glove and stocking" pattern. This article examines advances that facilitate the early detection of DPN and evaluates the evidence for early multiple risk factor management techniques to ameliorate DPN.